2023
DOI: 10.1039/d2tb02596e
|View full text |Cite
|
Sign up to set email alerts
|

Smart microneedle patches for wound healing and management

Abstract: Diagram of the Smart Wound Management Microneedle Patch. Smart microneedle patches combine treatment and monitoring for real-time diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 215 publications
0
9
0
Order By: Relevance
“…Wound healing is a dynamic and continuous process that mainly includes four stages: hemostasis, inflammation, proliferation, and remodeling. 16 When the skin is damaged, the first thing that occurs is the hemostasis process, where capillaries quickly contract and platelets initiate a coagulation cascade reaction to quickly reduce blood flow and seal the wound. In addition, platelets directly capture immune cells or release chemokines to attract immune cells to the injured site, preparing for the subsequent inflammatory stage.…”
Section: Physiological and Pathological Wound Healing Processmentioning
confidence: 99%
“…Wound healing is a dynamic and continuous process that mainly includes four stages: hemostasis, inflammation, proliferation, and remodeling. 16 When the skin is damaged, the first thing that occurs is the hemostasis process, where capillaries quickly contract and platelets initiate a coagulation cascade reaction to quickly reduce blood flow and seal the wound. In addition, platelets directly capture immune cells or release chemokines to attract immune cells to the injured site, preparing for the subsequent inflammatory stage.…”
Section: Physiological and Pathological Wound Healing Processmentioning
confidence: 99%
“…51 Growth factors such as platelet-derived growth factor (PDGF), VEGF, and recombinant human epidermal growth factor (rh-EGF) are essential for angiogenesis. 52,56 Inspired, Xu et al reported a gelatin MN patch loaded with PDGF to promote VEGF expression and accelerate angiogenesis at the wound site. 57 Chi et al introduced a VEGF-loaded responsive CS-pNIPAM MN patch that responds to localized high temperature in diabetic wounds, releasing VEGF and enhancing angiogenesis (►Fig.…”
Section: Mns With the Ability To Promote Angiogenesismentioning
confidence: 99%
“…Angiogenesis may be accelerated by sufficient oxygen. 52 53 54 Zhang et al explored an oxygen-responsive hemoglobin (Hb)-separated MN patch that could release oxygen responsively, thereby accelerating angiogenesis when it was applied to a diabetic wound ( Fig. 4A ).…”
Section: Designs Of Mn Patches For Diabetic Wound Treatmentmentioning
confidence: 99%
“…2 Microneedles (MNs), painless and active transdermal delivery devices, have been widely investigated and applied for cancer treatment, vaccination, and wound healing by transporting molecules with a molecular weight larger than 500 Dalton. 3–5 MNs can be categorized into hollow microneedles, coated microneedles, hydrogel microneedles, and dissolving microneedles based on the matrix materials and mechanisms. 6–9 However, most of them require complicated fabrication procedures or have limited drug-loading capacities.…”
Section: Introductionmentioning
confidence: 99%